Leigh syndrome caused by mutations in MTFMT is associated with a better prognosis. Issue 3 (17th February 2019) - Hayhurst, Hannah; de Coo, Irenaeus F. M.; Piekutowska‐Abramczuk, Dorota; Alston, Charlotte L.; Sharma, Sunil; Thompson, Kyle; Rius, Rocio; He, Langping; Hopton, Sila; Ploski, Rafal; Ciara, Elzbieta; Lake, Nicole J.; et al.
Abstract: Objectives: Mitochondrial methionyl‐tRNA formyltransferase (MTFMT) is required for the initiation of translation and elongation of mitochondrial protein synthesis. Pathogenic variants in MTFMT have been associated with Leigh syndrome (LS) and mitochondrial multiple respiratory chain deficiencies. We sought to elucidate the spectrum of clinical, neuroradiological and molecular genetic findings of patients with bi‐allelic pathogenic variants in MTFMT . Methods: Retrospective cohort study combining new cases and previously published cases. Results: Thirty‐eight patients with pathogenic variants in MTFMT were identified, including eight new cases. The median age of presentation was 14 months (range: birth to 17 years, interquartile range [IQR] 4.5 years), with developmental delay and motor symptoms being the most frequent initial manifestation. Twenty‐nine percent of the patients survived into adulthood. MRI headings in MTFMT pathogenic variants included symmetrical basal ganglia changes (62%), periventricular and subcortical white matter abnormalities (55%), and brainstem lesions (48%). Isolated complex I and combined respiratory chain deficiencies were identified in 31% and 59% of the cases, respectively. Reduction of the mitochondrial complex I and complex IV subunits was identified in the fibroblasts (13/13). Sixteen pathogenic variants were identified, of which c.626C>T was the most common. Seventy‐four percent of the patients were alive at their last clinical review (median 6.8 years, range: 14 months to 31 years, IQR 14.5 years). Interpretation: Patients that harbour pathogenic variants in MTFMT have a milder clinical phenotype and disease progression compared to LS caused by other nuclear defects. Fibroblasts may preclude the need for muscle biopsy, to prove causality of any novel variant.